Etika Komunikasi di Media Sosial - Astajaya, I Ketut Manik (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
This paper discusses the Ethics of Communication on Social Media. Humans as social beings, of course through the process of communication in everyday life. The communication process is carried out using existing media roles. As technology develops, media development becomes more sophisticated. One of them is the existence of social media. At present, the process of communication has become even easier, so it is known as media communication, which in this study is through social media. In using social media, of course, it can't be done at will, but there is a communication ethic that needs attention.Communication ethics in social media will be reviewed by researchers. In this digital age, the development of social media has entered into life today. Social media seemed to be a place to spill stories of all activities, emotional outburst in the form of writing or photos that often overrides the existing ethics. Social media is no longer a medium to facilitate communication to share information, but more dominant to be a container to accommodate sensations. If technological advancements are not accompanied by advances in thinking, the existing technological advances are inversely proportional in terms of thinking patterns.